1990
DOI: 10.1128/aem.56.11.3329-3336.1990
|View full text |Cite
|
Sign up to set email alerts
|

Localization of inulinase and invertase in Kluyveromyces species

Abstract: In vivo hydrolysis of inulin and sucrose was examined in selected yeasts of the genus Kluyveromyces. Cells, grown in sucrose-limited chemostat cultures, were subjected to treatments for the removal of inulinase, the enzyme responsible for the hydrolysis of both inulin and sucrose. The effects of these treatments were studied by measurement of inulin-dependent and sucrose-dependent oxygen consumption by cell suspensions. In Kluyveromyces marxianus var. marxianus, inulinase was partially secreted into the cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…ficuurn. On the other hand, the data are significantly different from those obtained by Rouwenhorst et al (1990a) and Workman and Day (1983) concerning inulinases isolated from Kluyveromyces species (50°C and p H 4-5) and invertase from S . cerevisiae (37°C and p H 4-5).…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…ficuurn. On the other hand, the data are significantly different from those obtained by Rouwenhorst et al (1990a) and Workman and Day (1983) concerning inulinases isolated from Kluyveromyces species (50°C and p H 4-5) and invertase from S . cerevisiae (37°C and p H 4-5).…”
Section: Resultscontrasting
confidence: 95%
“…A considerable amount of information has been devoted to /?-fructosidases (invertase E.C.3.2.1.26) and inulinases (E.C.3.2.1.7) of yeasts (Parekh and Margarits 1986;Esmon et al 1987;Rouwenhorst et al 1990a) and molds (Ettalibi and Baratti 1987;Uhrn et al 1987) but only a few studies reporting /?-fructosidase activity in bacteria have been done (Efstathiou et al 1986;Allais et al 1987), except for Bacillus species (Uhm et al 1985;Allais et al 1987;Vullo et al 1991). These enzymes have potential use in the preparation of fructose syrups from inulin and invert sugar from sucrose in the food industry (Monsan and Combes 1984;Vullo et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the S. cerevisiae SUC2 sequence hardly hybridized with the genome of the yeast S. kluyveri UCD 51-242 (6). Further research into the nature of the sucrose-hydrolyzing activity of S. kluyveri showed that this yeast possesses an inulinase, as defined by S/I ratio and behavior on native gel electrophoresis (31).…”
Section: Discussionmentioning
confidence: 99%
“…marxianus NRRLy2415, a strain which has previously been shown to be dimorphic in character (Walker and O'Neill, 1990). K. marxianus is extensively used for the fermentation of cheese whey permeate to ethanol (Vienne and von Stockar, 1985) and also possesses a wealth of hydrolytic enzymes, including galactosidase (Ku and Hang, 1992), inulinase (Rouwenhorst et al, 1990), and polygalacturonases (Schwan and Rose, 1994).…”
Section: Introductionmentioning
confidence: 99%